The Sense of Belonging as a Catalyst for Retaining Millennial Employees in the Hospitality Sector (International Journal of Economics and Management Research, 2026)
High turnover rates among millennial employees remain a critical challenge for the hospitality industry. This study aims to analyze the effect of internal branding on millennial employees' retention intention with sense of belonging as a mediating variable in hotels in Semarang Regency. Using a mixed-methods sequential explanatory design, data were collected from 156 respondents through questionnaires and 14 key informants through in-depth interviews. Quantitative analysis employed PLS-SEM using SmartPLS 4.0, while qualitative data were analyzed through thematic analysis. The findings revealed that internal branding has a significant positive effect on sense of belonging (β=0.687, p<0.001) and retention intention (β=0.289, p<0.001). Sense of belonging partially mediates this relationship with VAF of 56.3% and R² of 58.3%. Qualitative findings identified four key themes: authentic value communication, empowering leadership, meaningful career development, and supportive work community. This study contributes to the development of social identity theory in the context of hospitality internal branding and provides practical implications for millennial employee retention strategies